Tendências contemporâneas da política de assistência social : uma análise das transformações ocorridas na concepção de assistência social no Brasil - Campos, Naara de Lima (2012)
This work brings together the elements that compose the current conception of social assistance in Brazil, after the promulgation of the 1988 constitution when welfare was first recognized as a right of citizenship and legal duty of the state, guaranteed by the Supreme Law. In this law the welfare presupposed a logic of full employment, intended therefore unable to give priority to the job. However, in a context of structural unemployment that is understood in terms of security guarantees, seeking to take the social protection of those able to work, in view of the deterioration in the labor market, restricted opportunities and income and growth Progressive unemployment and informality. The central idea is that this is a critical description of the design of social assistance in Brazil, discussing each of their arguments more explicit in order to reveal an intentionality linked to a perspective of state. We use the term design in order to conceive, think, feel, understand or interpret something. Social assistance today, responds to a unique process that combines historical, economic, political, social and ideological in this sense, represents a world view and a social project, championed by the ruling class, guided by the exploitation of labor. The current conception of social assistance follows therefore a new form of social policy from the perspective of human development and poverty reduction in which great emphasis has been to withdraw discussions intervention in poverty and the scope of the social question, allocating the in individuals and in their "disability". Social assistance to take responsibility or co-responsibility in developing capacities of individuals indicates the tendency of a new conception of social welfare.